Novel Active Current Transducers for Diesel Power Stations - Denis B. Solovev; Alena E. Merkusheva (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
Autonomous diesel power plants found the active application at the organization of autonomous power supply of the mining enterprises. In article the problem of increase of efficiency of use of control units is considered by the active power of synchronous generators of diesel power plants. As a solution the new innovative offer in the form of the developed device of the measuring converter of active current which is one of the main components of game-trolno-measuring equipment of diesel power plants is offered. The developed scheme is simpler, in comparison with the similar converters of active current executed on the basis of current transformers. In the developed scheme of the measuring converter it is offered to use the differentiating induction converters of current as primary measuring converters. It allows to reduce many times number of the elements entering the standard scheme, and also mass-dimensional characteristics of the device.